Molecular Modelling in Biosensor Desgin for Cholera Toxin Detection - Cinaroglu, Selim; Anac, Ilke; Kok, Fatma Nese; Ildeniz, Tugba Arzu Ozal (IEEE, 2017)
In undevelped countries waterborn epidemics are significantly threatening for health. Cholera is one of the main such diseases. For the initiation of preventive health care services, studies for designing biosensors that detects the cholera toxin which is the cause of this disease is necessary. Besides the experiments performed during the design which uses SPR and SPFS technology, usage of computational biology takes an important place. Investigation of the binding mechanisms taking place in the biosensor is possible at the atomistic scales by molecular modelling techniques and this going to be a preliminary work for the similar biosensor designs. In this research, ligands enable the detection by ensuring the specific binding of cholera toxin B (Ch B) were determined by the computation of binding energies and binding positions and interactions were investigated.
21st National Biomedical Engineering Meeting (BIYOMUT) -- NOV 24-DEC 26, 2017 -- Istanbul, TURKEY